TCP over geo-routing for high mobility: vehicle grids and airborne swarms - Chen, Jiwei (2006)
Ad hoc wireless networks have become the architecture of choice for peer to peer communications in areas where the telecommunications infrastructure is inadequate or has failed. A major challenge is the reliable delivery of data when nodes move. The reliable Internet protocol is TCP. However, TCP performs poorly in mobile ad hoc networks, mainly because of route breakage. To overcome this problem, a robust routing protocol must be used. To this effect, Geo-routing has recently received attention in large scale, mobile systems as it does not require end- to-end path establishment and pre-computed packet forwarding routing structure at nodes. These properties make Geo-routing robust to highly dynamic route changes. For best performance, however, several parameters must be carefully tuned. In this paper we study the joint optimization of TCP and Geo-routing parame- ters to handle high speeds. We first introduce two highly mobile ad hoc scenarios that require reliable delivery, namely the vehicle urban grid and the airborne swarms. Then, we study the impact of critical system parameters (e.g., hello message ex- change rate, delay timer in TCP for out-of-order delivery, etc) on the performance of both UDP and TCP. We improve hello message effciency in Geo-routing by using an adaptive hello exchange scheme. Then, we fix the out-of-order problem in TCP by using a receiver-side out-of-order detection and delayed ack strategy. We show that these parameter adjustments are critical for effcient TCP over Geo-routing in highly mobile applications. With these enhancements our TCP with Geo-routing solution easily outperforms TCP over traditional ad hoc routing schemes, such as AODV.